Projeto e construção de um bioreator para síntese orgânica assimétrica catalisada por saccharomyces cerevisiae (fermento biológico de padaria) - Pereira, Ricardo de Souza [UNESP] (1997)
A model for the construction of a simple and cheap apparatus to be used as bioreactor for reactions catalyzed by baker's yeast (Saccharomyces cerevisiae) is described. The bioconversion and separation of cells from products and residual substrates are obtained at the same time. The reactions carried out in this type of reactor are faster than those catalyzed by immobilized cells. Yeast cells can be cultivated in this bioreactor operating with cell recycling at appropriated conditions using glucose and other nutrients.